Hubungan Komorbiditas dengan Mortalitas Pasien Diabetes Melitus di Ruang Intensive Care Unit (ICU) - Tri Sakti Wirotomo; Dwi Fijianto; Firman Faradisi; Yuni Sandra Pratiwi (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
Diabetes melitus is a group of metabolic diseases characterized by hyperglicemia that occurs due to abnormalities in insulin secretion, insulin action or both. Diabetes melitus patients can experience a decline in health status which results in physiological changes that require treatment in an intensive care unit. Apart from causing complications, diabetes melitus also causes deterioration ogf the body’s system if the patien suffers from comorbidities. This study aim to determine the relationship between comorbidities and mortality in diabetes melitus patients treated in the intensive care unit. The research method is observational with a croos-sectional design. Sampling used total sampling. Data was obtained secondary data in form of medical records in the ICU room at Kajen Hospital, Pekalongan Regency in January-December 2022. The number of respondents was 40 diabetes melitus patients. Data analysis used the Pearson correlation statistical test to determine whether there are wasvrelationship between comorbidity and respondent mortality. The research results obtained a p-value of 0,022 (<0,05). The conclusion from this study is that there is a relationship between comorbidity and mortality of diabetes melituspatients in the intensive care unit of Kajen Regional Hospital, Pekalongan Regency.